Disability among Palestinian elderly in the occupied Palestinian territory (oPt): prevalence and associated factors - Nouh Harsha; Luay Ziq; Rita Giacaman (BMC, 2019)
Abstract Background Disability poses an important challenge to countries all over the world since it affects more than 15% of the global population. The disability prevalence is higher in developing countries compared to developed ones. Disability has negative consequences on health, wellbeing, and quality of life. The goal of this study is to assess the prevalence of disability and to determine some of its associated factors among Palestinian elderly in the occupied Palestinian territory (oPt), a country marked by a chronic lack of political, economic, and social stability which affect various aspects of the population's life. Methods We used data from the Palestinian Central Bureau of Statistics (PCBS) disability survey conducted in 2011 using a nationally representative sample of the Palestinians living in the West Bank (WB) and Gaza Strip (GS). Data were collected using a standardized questionnaire developed and adopted by the World Health Organization (WHO) and the Washington Group (WG) for Disability Statistics, adapted to satisfy the Palestinian context. Results Overall, 31.2% of the Palestinian elderly 60 years and above reported one or more type of disability. Binary logistic regression with disability as the dependent variable showed that older people [OR = 2.88, 95% CI: 2.31-3.60], women [OR = 1.65, 95% CI: 1.33-2.04], illiterate people [OR = 2.37, 95% CI: 1.83-3.06], people reporting small family sizes with 1 to 2 members [OR = 1.69, 95% CI: 1.34-2.14], people who reported that they were not working at the time of the survey [OR = 4.59, 95% CI: 3.13-6.73], and Palestinian refugees [OR = 1.22, 95% CI: 1.04-1.42] were more likely to have a disability. However, residents of the Centre of WB were less likely to have disability compared to residents of the GS [OR = 0.46, 95% CI: 0.37-0.58]. Conclusions The study found a high prevalence of disability among Palestinian elderly, as has been reported by the majority of studies performed in developing countries. However, results indicate that demographic and socioeconomic differences among the disabled should be taken into special consideration in setting policies and practices to improve the health and wellbeing of the disabled.